Drivers and Barriers to Medication Adherence in Patients with Chronic Myeloid Leukaemia: A Qualitative Study - Gitte Lee Mortensen; Jindrich Mourek (Journal of Hematology and Oncology Research, 2017)
With the introduction of tyrosine kinase inhibitors (TKI), patients with chronic myeloid leukemia (CML) have obtained survival rates close to normal. It may appear paradoxical, then, that medication adherence is suboptimal in some health care settings. As the first of its kind, this study aimed to explore drivers and barriers to TKI treatment adherence in Danish CML patients. A literature study informed the design of qualitative interviews with 20 patients, individually and in focus groups, focusing on their disease perceptions of CML, their health-related quality of life (QoL) and medication adherence. The study showed that many participants had previously switched treatment due to lacking efficacy or intolerance but most felt their current disease burden was tolerable. Anxiety might, however, resurface if treatment stopped working or with the occurrence of infections or side effects, creating a state of ‘fragile peace’. To these patients, their role functioning – as professionals, spouses, parents and grandparents – was crucial to uphold a positive self-image and meaningful life. Whether treatment enabled or hindered this was thus decisive to their QoL and medication adherence. Our participants expressed high adherence rates with only one having intentionally non-adhered due to side effects and poor QoL. Most participants felt well-informed about CML and treatment and privileged to receive specialised personal care from the public health care system acting to motivate their medication adherence. As a novel finding, this study indicates that the prospect of treatment-free remission may positively affect ‘adherence’ suggest this should be explored in future studies.
Keywords: Chronic Myeloid Leukemia